The Independence Judge Verdict in Tax Dispute Resolution - Sartono Sartono; Tumanggor Tumanggor; Sri Soemantri; Wiratni Ahmadi; Satya Arinanto (Postgraduate of Jayabaya University, 2015)
Tax tribunal as a specialized court exercising judicial powers to investigate and adjudicate tax disputes still using a system of dualism coaching, because until now there has been no revision or amendment of Law No. 2 of 2002 on the Tax tribunal. Independence and freedom of the Tax tribunal judge in deciding tax disputes must uphold justice, and not subject to and bound by any party. This research using theory of Justice based on the Pancasila. Grand Theory, theory of the State of Law as the Middle Range Theory and an Independent Judicial Power Theory. Applied Theory. This research was conducted using a normative juridical. Based on the research results show that the Tax tribunal judge in examining and deciding tax disputes has been carrying out its obligations which reflect the independence and the independence of judges and impartially and has fulfilled the principles of independent judicial power, in accordance with the provisions of Article 24 of the 1945 Constitution.